A SAMAPTA UNIT DIALOGICAL PATROL EFFORT TO PREVENT CRIME OF CURRENCY IN THE JURISDICTION OF SUKOHARJO POLICE - R.RIZQI AGUNG BIMANTORO SUKENDRO (Police Studies Review, 2022)
Motor vehicle theft is one of the most common crimes in Indonesia. Theft is a crime that often occurs in the Sukoharjo Regency. Dialogic patrol is a police activity that is preventive in nature against theft. This is the background for the author to examine the implementation of the Dialogical Patrol of the Sukoharjo Police. This study aims to find out how the implementation, the influencing factors and what efforts can improve the performance of the Samapta Unit dialogical patrols to prevent theft at the Sukoharjo Police. The research approach used is qualitative. A qualitative approach is used so that the data obtained is more comprehensive, valid, reliable and objective. The object of the research is the implementation and personnel of dialogical patrols in the Sukoharjo Police Samapta Unit. This research was conducted for two weeks with research instruments in the form of interview guidelines, observation sheets and document review. Based on the results of interviews, observations and research data processing at the Sukoharjo Police Samapta Unit, it was stated that the quality of human resources was still lacking, the budget was not accurate, standard operating procedures were not implemented and the infrastructure was lacking support. In addition, the lack of knowledge and skills of the Patrol Unit of the Samapta Unit and the geographical conditions of Sukoharjo Regency. Based on the results of the data research, it was concluded that the implementation of dialogical patrols by the Samapta Unit at the Sukoharjo Police was not in accordance with the Perkabaharkam and efforts to improve the performance of the Sukoharjo Police Samapta Unit personnel were not maximized due to internal factors, namely human resources, budget, standard operating procedures and infrastructure and external factors including community and geographical conditions of Sukoharjo Regency. Keywords: Efforts, Dialogic Patrol, Samapta Unit, Motor Vehicle Theft